Karakterisasi Tanah Vulkanik di Kabupaten Kediri, Jawa Timur, Indonesia Berdasarkan Uji CPT, SPT, dan PMT: Site Characterization of Volcanic Soil in Kediri Regency, East Java, Indonesia Based On CPT, SPT, and PMT - Wiwarsono, Fransisko; Rahardjo, Paulus Pramono; Sadisun, Imam Achmad (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
Indonesia is a country surrounded by the Pacific Ring of Fire so that various areas are dominated by volcanic soil. Volcanic soils have unique and unusual characteristics, different structures and properties from soil in general, and are strongly influenced by geological processes. Volcanic soils were also found to be problematic and caused a lot of geotechnical damage. Research on volcanic soils from a geotechnical perspective in Indonesia is still very limited. This study aims to characterize volcanic materials in Kediri Regency, East Java, Indonesia, based on in situ testing using CPT (Cone Penetration Test), Standard Penetration Test (SPT), and Pressuremeter Test (PMT). CPT and SPT are the most common and frequently used field tests, while PMT is used to obtain horizontal stresses. Some data from the X-Ray Diffraction Analysis (XRD) test and corebox drilling results will also be used in this study. Field test results will display soil classification and parameters, which will then be combined, and empirical correlations will be obtained for site characterization as well as comparisons with other volcanic soil literature studies. The results showed that the volcanic soil in Kediri Regency consists of non-lateritic to lateritic soil. Based on the CPT and SPT correlations, it was found that the qc/N value was greater than in general soils for both cohesive and non-cohesive soils. The authors also found a relationship between parameters and interpretation of PMT data against NSPT for cohesive volcanic soils in the study area.